Cell-to-Cell Variation in Gene Expression for Cultured Human Cells Is Controlled in Trans by Diverse Genes: Implications for the Pathobiology of Aging. (20th January 2020) - Zhang, Jiaming; Burnaevskiy, Nikolay; Annis, James; Han, Wenyan; Hou, Deyin; Ladd, Paula; Lee, Lin; Mendenhall, Alexander R; Oshima, Junko; Martin, George M
Abstract: Cell-to-cell variation in gene expression increases among homologous cells within multiple tissues during aging. We call this phenomenon variegated gene expression (VGE). Long, healthy life requires robust and coordinated gene expression. We posit that nature may have evolved VGE as a bet-hedging mechanism to protect reproductively active populations. The price we may pay is accelerated aging. That hypothesis will require the demonstration that genetic loci are capable of modulating degrees of VGE. While loci controlling VGE in yeast and genes controlling interindividual variation in gene expression in Caenorhabditis elegans have been identified, there has been no compelling evidence for the role of specific genetic loci in modulations of VGE of specific targets in humans. With the assistance of a core facility, we used a customized library of siRNA constructs to screen 1, 195 human genes to identify loci contributing to the control of VGE of a gene with relevance to the biology of aging. We identified approximately 50 loci controlling VGE of the prolongevity gene, SIRT1 . Because of its partial homology to FOXO3A, a variant of which is enriched in centenarians, our laboratory independently confirmed that the knockdown of FOXF2 greatly diminished VGE of SIRT1 but had little impact upon the VGE of WRN . While the role of these VGE-altering genes on aging in vivo remains to be determined, we hypothesize that some of these genes can be targeted to increase functionality during aging.